Colorectal cancer mortality in persons with severe mental illness: a scoping review with meta-analyses of observational studies - Paula R. Pop; Gitte S. Larsen; Mette K. Thomsen; Christoffer Johansen; Robert Zachariae; Bolette Skjødt Rafn (Acta Oncologica)
Background and purpose: Persons with severe mental illnesses (SMIs) have reduced participation in colorectal cancer (CRC) screening programs, higher odds of advanced stage at diagnosis, and are less likely to receive adequate treatment than the general population. It remains unclear to what extent these factors impact CRC outcomes for persons with SMI. The aim of this scoping review was to describe and quantify CRC mortality for persons with SMI compared with the general population.